Influence of Hygrothermal Aging on the Strength of Carbon Fiber Reinforced Compo-site Material Equipment Cabin - HE Zikun; XIAO Shoune; Jiang Lanxin; CHEN Dongdong; WANG Mingmeng (Chengshi guidao jiaotong yanjiu)
［Objective］The operating environment of rail transit trains is relatively complex, and composite materials on the trains are subject to deterioration during operation due to the aging phenomenon caused by harsh external factors. Therefore, it is necessary to study the effect of hygrothermal aging on the strength of carbon fiber composite equipment cabins. ［Method］Hygrothermal aging tests and static mechanics (tensile, compression, shear) tests on carbon fiber composite are conducted to obtain their mechanical performance parameters before and after hygrothermal aging. An equipment cabin finite element model for a certain type of carbon fiber composite is established. The material parameters before and after hygrothermal aging are obtained by experimental methods, and the static strength of the equipment cabin under aerodynamic loads is calculated. ［Result & Conclusion］The mechanical properties of woven carbon fiber composites after hygrothermal aging show different degrees of attenuation, with the compressive strength decreasing the most by 39.3%; compared with the initial state, the Tsai-Wu failure factors of each carbon fiber component show different degrees of increase. The degradation of carbon fiber strength and carbon fiber modulus due to the hygrothermal aging may cause the degradation of equipment cabin stiffness and bearing limit.